A study of the different factors affecting the academic performance of the class '80 students of the College of Dentistry University of the Philippines Manila - Cheng, Leonila K.; Chua, Ruby G.; Marquez, Eleuteria (Adviser).
This is a study of the factors affecting the academic performance of the dental students of class '80 of the University of the Philippines, College of Dentistry, Questionnaires were given out to the class to be answered. Upon collection of the data, the tally and score method was used to organize the data. Thereafter, they were presented in tabular form. Then the list of factors were tested for their significance and subsequently, the categories were ranked. The conclusion of the study is that the factors that were proven significant and affected the academic performance of the class '80 dental students are the following: Age, dentistry as primary choice of career, high school attended, blood race, and travel time.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.